Autoestima y la conducta agresiva en los estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Pizanan Ortiz, Johanna Alexandra (2025)
The aim of this research is to establish the relationship between the levels of self-esteem and aggressive behavior of sixth semester students of the Psychopedagogy course at the National University of Chimborazo, Riobamba. The two variables under study currently have a great impact on lives of all people, especially on the social development of students, regardless of the level they are at. Self-esteem is the fundamental engine that drives the search for approval and positive recognition of oneself. On the other hand, aggressive behavior can emerge throughout life as we face various frustrations that fuel feelings of aggression. This aggressiveness can be expressed directly towards those who provoke this frustration, either through physical or verbal aggression, or indirectly, by transferring the aggression towards a third person or an object. A quantitative approach methodology was used, with a non-experimental design. This study was classified as field and cross-sectional research; the level of research was descriptive and correlational. The target population of the study consisted of the Psychopedagogy students at the Universidad Nacional de Chimborazo; the sample used was non-probabilistic and intentional, composed of 33 university students of the sixth semester. The techniques applied were the Buss-Perry Aggressiveness Test and the Rosenberg Self-Esteem Scale. The results of the study revealed that mosto f the students present a low level of self esteem; which correlates with a medium-high level with respect to aggressiveness. In addition, significant levels of physical aggressiveness and hostility were identified, showing a significant positive correlation between both variables. In conclusion, this research reflects the importance of self-esteem and aggressive behavior, because if a student has a low level of self-esteem he or she tends to lose control of his emotions and when facing a compliment or criticism may react inappropriately, which in turn can trigger aggressive behavior.